THE THEORY OF AL-MISBAH ON SUBSIDIZED GAS DISTRIBUTION: A Case Study of Banda Raya Sub-District, Banda Aceh, Indonesia - Farah Saima; Faisal Fauzan (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The distribution of 3-kg subsidised LPG gas is part of the government’s policy to meet the energy needs of low-income communities. However, in practice, this distribution often faces various problems such as mistargeted allocation, hoarding, and fraud within the supply chain. These conditions demand strict and continuous supervision from various parties, including distribution agents. This study aims to analyse the realisation of subsidised LPG gas distribution oversight by PT Mitra Alam Jaya in Banda Aceh from the perspective of al-hisbah theory. In Islam, al-hisbah provides a normative and structural framework for the function of economic supervision, ensuring justice and preventing wrongdoing. This research employs a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews with the owners and managers of the distribution agency, as well as field observations and documentation. The results show that PT Mitra Alam Jaya has implemented a standardised distribution and supervision system, including distribution records, stock monitoring, and routine reporting. However, challenges remain, including weak oversight at lower levels, a lack of moral control among distribution actors, and limited synergy with independent supervisory institutions. From the perspective of al-hisbah, a systematic supervisory system reflects the principles of amar ma’ruf nahi munkar and distributive justice. This study recommends strengthening supervision based on hisbah values, increasing moral education, and enhancing transparency in distribution data to achieve fair LPG governance.